Early Nonparental Care and Social Behavior in Elementary School: Support for a Social Group Adaptation Hypothesis. Issue 5 (September 2015) - Pingault, Jean‐Baptiste; Tremblay, Richard E.; Vitaro, Frank; Japel, Christa; Boivin, Michel; Côté, Sylvana M.
<x xml:space="preserve">Abstract</x> This study examined the contribution of nonparental child‐care services received during the preschool years to the development of social behavior between kindergarten and the end of elementary school with a birth cohort from Québec, Canada (N = 1, 544). Mothers reported on the use of child‐care services, while elementary school teachers rated children's shyness, social withdrawal, prosociality, opposition, and aggression. Children who received nonparental child‐care services were less shy, less socially withdrawn, more oppositional, and more aggressive at school entry (age 6 years). However, these differences disappeared during elementary school as children who received exclusive parental care caught up with those who received nonparental care services. This "catch‐up" effect from the perspective of children's adaptation to the social group is discussed.